Relationship between retention factors and affective organisational commitment among knowledge workers in Malaysia - Ahsan, Nilufar; Fie, David Yong Gun; Foong, Yeap Peik; Alam, Syed Shah (Journal of Business Economics and Management, 2013)
This research explores the issues that influence affective commitment among knowledge workers in Malaysia. The determinants of affective commitment among knowledge workers that have been examined from the Malaysian knowledge workers’ perspective under this study including compensation, career opportunity, training and development, supervisor support, job autonomy, work life policies and skill varieties. A conceptual framework is constructed based on the retention factors and research hypothesis are then developed in order to focus attention on sets of factors that influences affective commitment among knowledge workers in Malaysia. Results of regression analyses revealed that all but supervisor support and skill variety were significant predictors of affective commitment among knowledge workers in Malaysia. Recommendations for future research are presented for industry bodies involved in supporting retention of knowledge workers in Malaysia.